Contemporary public policies to strengthen family farming in the international perspective: A bibliometric study - Everaldo Veres Zahaikevitch; Luciano Medina Macedo; Leomara Battisti Telles; Juliana Vitória Messias Bittencourt; Andréia Gura Veres Zahaikevitch (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Family farming produces most of the fresh food consumed in large urban centers. However, its success depends on a variety of public policies, which range from strengthening the means of production to supporting marketing channels. In this article, we conduct a careful bibliometric analysis of studies in the international literature that address "family farming, public policies, and socioeconomic development". The aim of the study is to identify and classify the public policies aimed at supporting family farming and socioeconomic development. We carried out a systematic literature review considering five international scientific journal databases using pairs of the keywords "public policies", "family farming" and "socioeconomic development". The resulting sample was a total of 625 articles, covering the period between 1984 and 2020. A bibliometric analysis of the first 50 articles selected by the Methodi Ordinatio tool was performed. For the final portfolio, 10 variables were analyzed to better assess and understand the current literature. Our analysis shows an increase in publications in the last five years, with articles from South America being more prevalent than those from other continents. Brazil being one of the key countries that has developed public policies aimed at family farming and rural socioeconomic development.
Keywords: 650; bliometry; family agriculture; Methodi Ordinatio; public policies; socioeconomic development